Penanaman Nilai-nilai Pendidikan Karakter Melalui Kegiatan Kepramukaan di Madrasah Tsanawiyah - Wahyu Sudrajat (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
Character education can be widely described as a school-based process to promote personal development in youth, through the development of virtue and moral values. This paper describes how scoutmasters of MTS Tribakti Al-Iklas 2 Anak Tuha Central Lampung have infused the character education values on scout activities at this school. This study uses qualitative methods, with a case study approach. The data were collected through observation, interview, and documentation. The collected data were then analysed descriptively by using three ways namely data reduction, data presentation, and conclusion or verification. The results show that the infusing of characer education through actualization model scouting activities in collaboration with teachers as well as block models that have been programmed at the beginning of the school year, such as camps and nature exploration. The characters that can be formed are patience, cooperation, responsibility, social care, courage, confidence, perseverance, creative, religious, patriotism, environmental awareness, independence, discipline and hard work. Terefore, it needs a collaboration scoutmasters of with parents student to to succeed the scouting program. For future research, it is recommended to to probe parent's role in supporting students' scouting activities.